The biological transformation of ammonium and urea in a eutrophic estuarine system in Southern China - Jin-Ming Tang; Min Nina Xu; Yuxuan Lin; Huangxin Chen; Haoquan Jin; Li-Li Han; Wenbin Zou; Shuh-Ji Kao (Frontiers in Marine Science, 2022)
Estuaries channel large amounts of anthropogenic nitrogen (N) from continents to the offshore where productivity is widely limited by N and phosphorus. Ammonium and urea, two reduced forms of anthropogenic N commonly observed, are the preferred substrates for various microorganisms (e.g., uptake by phytoplankton or bacteria and oxidation by nitrifier). Yet, it remains underexplored how they transform and their concentrations vary during transport in the estuary which may influence the offshore microbial community. We applied 15 N isotope tracer incubation techniques to determine the two main bio-consumption processes, i.e., uptake and oxidation, of ammonium and urea, in the dark for the Jiulong River Estuary, a eutrophic estuary in southeastern China. Results showed that light penetration depth ranged from 0.8-3.3 m leaving 76% of estuary water bodies to stay in dark situations throughout a day. Ammonia oxidation, which favors dark conditions, dominates the estuarine regenerated-N cycle, showing the rank: ammonia oxidation > ammonium uptake >> urea uptake ≈ urea oxidation. By compiling the reported case studies, we found the relatively low ratio of urea oxidation to ammonia oxidation was accompanied by a relatively high ammonium concentration. Microorganisms’ high preference for ammonium over urea may lead to an inhibitory-like phenomenon. An analogous effect was evident by the increased urea uptake at downstream when ammonium was down to a few µM. The obstructed urea utilization resulted in 10 times longer lifetime for urea relative to ammonium (surface: 19 ± 9 days; bottom 12 ± 7 days). Such an inhibitory-like effect allows urea to be preserved in the estuary and allows urea to be transported farther offshore to stimulate microorganisms capable of utilizing urea, which may have significant impacts on offshore ecology.